Nilai Historis Isi Prasasti Telaga Batu Dalam Sistem Pemerintahan Kedatuan Sriwijaya - Widya, Widya; Sholeh, Kabib; Wandiyo, Wandiyo (PPSDP Undergraduate Journal of Educational Sciences, 2025)
The Sriwijaya Kingdom was one of the first maritime powers recorded in Indonesian history, located in the city of Palembang. The Sriwijaya Chiefdom has a relic, one of which is the Telaga Batu Inscription. The Telaga Batu Inscription is one of the relics of the Srivijaya chiefdom. The Telaga Batu Inscription contains a curse that those who violate the rules of the datu will be punished and cursed. The aim of this research is to determine the historical value of the contents of the Telaga Batu Inscription in the political field, the value of firmness and justice, as well as the value of the government system. The research method used in this research is using the Qualitative Descriptive method and for data collection using library research techniques (library), data collection, then using data verification or source criticism, and data analysis techniques using historical interpretation or historical interpretation and the final step is Historiography. The results of this research explain that one of the relics of the Sriwijaya chiefdom is the Telaga Batu inscription, the contents of the Telaga Batu inscription have historical value in the political field, the value of firmness and justice and also have the value of a government system.